The Role Of Ecology As A Science In The Social And Economic Development Of Uzbekistan - A.Sh. Kaipnazarov (International Scientific and Current Research Conferences, 2021)
This article discusses the main functions of modern applied ecology, formed on a broad complex basis, engaged in research, practical activities and contributing to the development of new areas of natural, technical and social sciences. In addition, ecology has the potential of “interdisciplinary” scientific activity, focusing all sciences on solutions and research in the relationship of all mankind and nature, in general, it also explores the creative assimilation of the most rational aspects of many sciences and scientific theories of global ecology in different countries of the world.